Nodal prices, capacity valuation and investments in natural gas markets: Overview and analytical framework - Stefan Lochner (Institute of Energy Economics at the University of Cologne (EWI), 2009)
Especially in the short-term, prices in natural gas markets are not exclusively determined by overall supply and demand, but also by the availability of the transport infrastructure. If transportation capacity is scarce, prices may form in (local) residual markets and can differ regionally. If available, storages provide intertemporal arbitrage possibilities which also impact prices. Temporal and regional price differences, in turn, determine the value of storage and transport capacity if either one is scarce. This paper applies an analytical framework for a simple pipeline grid with a storage over two periods to illustrate the interdependencies between prices, scarce capacity and capacity value. The theoretically optimal transportation and storage tariffs are described analytically. The optimal pipeline investment size is shown to be related to marginal storage investment and a function of the discounted and aggregated cost of congestion over the lifetime's asset.
Keywords: Q41; D41; L50; P42; 330; Natural gas; transport capacity; storage; investment; prices; Gaspreis; Gasleitungstransport; Netzzugang; Transportkapazität; Lager; Investition; Theorie